Determination of the nuclear radius parameter using the γ-ray spectrometer - Prashant N. Patil; G. B. Hiremath; A. Vinayak; M. M. Hosamani; V. P. Singh; N. M. Badiger (Ядерна фізика та енергетика)
The nuclear radius parameter of carbon, aluminium, iron, copper, and zinc nuclei has been determined by using (n,γ)-reaction. The neutrons from the americium-beryllium source are made to interact with the water moderator to produce the γ-rays of 2.2 MeV through (n,γ)-reaction. The γ-radiation emitted from the water medium is measured with a scintillation detector coupled to 8k multi-channel analyzer. The neutrons from the americium-beryllium source are allowed to transmit through carbon, aluminium, iron, copper, and zinc elemental targets of various thicknesses, and transmitted neutrons are again allowed to interact with water moderators to produce 2.2 MeV γ-radiation. By measuring the yield of γ-radiation produced in water moderators by neutrons transmitted through elemental targets of different mass number values, the total neutron interaction cross-sections are determined. By knowing the total neutron interaction cross-sections and mass number of the target nuclei, the radius parameter has been determined.